(untitled) (Research, Society and Development, 2022)
In dentistry, oral candidiasis is mainly caused by Candida albicans but non-albicans species are also emerging and antifungal resistance is increasing. Alternative therapies such as herbal medicine and photodynamic therapy (PDT) are promising in this regard. The study aimed to evaluate the action of Curcuma longa glycolic extract associated or not with light on Candida albicans, Candida krusei, and Candida glabrata biofilms. Monomicrobial biofilms of Candida species were formed for 48 h, followed by treatment with the isolated plant extract, plant extract associated with light (660 nm 123.4 MW/cm² 10 J/cm² or 25 J/cm²), group LED, saline and nystatin group. Cell viability was analyzed using the MTT test and and optical densities were transformed into percentage of metabolic activity. For statistical analysis, if the data met the assumptions, they were analyzed by ANOVA and Tukey’s test, otherwise, by the Kruskal-Wallis test and Dunn’s, considering a significance level of 5%. The C. longa extract applied or not to PDTa promoted significant antibiofilm action on the Candida species analyzed (p < 0.05), and the highest percentage of reduction was found on C. krusei, with reductions above 45%. In conclusion, the C. longa extract associated or not with PDTa showed antibiofilm action against Candida spp. and its antifungal activity was equal and even superior to that of nystatin on some species. The extract of C. longa proved to be a potent antifungal to be explored within alternative therapies in dentistry.